2007
DOI: 10.1088/0741-3335/49/12b/s61
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic laser-matter interaction: from attosecond pulse generation to fast ignition

Abstract: The field of laser-matter interaction has branched out in two main directions. The first, motivated by laser inertial confinement fusion, warm-dense-matter, fast ignition and astrophysics in laboratory, and the second driven by ultra-high intensity, exotic physics, high-energy particle, photon beam generation and time-resolved attosecond (zeptosecond) science. The degree of maturity from both experimental and theoretical stand-points is such that a large European infrastructure for each branch is contemplated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 27 publications
0
37
0
1
Order By: Relevance
“…Analytical calculations and simulations exploring this configuration have shown that an overdense e − e + plasma can be generated from a single electron by counter-propagating 100PW lasers [12][13][14][15]. Here we will show that such a plasma can be generated with an order of magnitude less laser power by firing the laser at a solid target, putting such experiments in reach of next-generation 10PW lasers [16].…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Analytical calculations and simulations exploring this configuration have shown that an overdense e − e + plasma can be generated from a single electron by counter-propagating 100PW lasers [12][13][14][15]. Here we will show that such a plasma can be generated with an order of magnitude less laser power by firing the laser at a solid target, putting such experiments in reach of next-generation 10PW lasers [16].…”
mentioning
confidence: 76%
“…Analytical calculations and simulations exploring this configuration have shown that an overdense e − e + plasma can be generated from a single electron by counter-propagating 100PW lasers [12][13][14][15]. Here we will show that such a plasma can be generated with an order of magnitude less laser power by firing the laser at a solid target, putting such experiments in reach of next-generation 10PW lasers [16].The dominant non-linear QED effects in 10PW laserplasma interactions are: synchrotron gamma-ray photon (γ h ) emission from electrons in the laser's electromagnetic fields; and pair-production by the multiphoton Breit-Wheeler process, γ h + nγ l → e − + e + , where γ l is a laser photon [3,17,18]. Each reaction is a strongly multiphoton process, the former process being non-linear Compton scattering, e − + mγ l → e − + γ h [19,20], in the limit m → ∞.…”
mentioning
confidence: 77%
“…The generation of attosecond pulses (APs) opens the possibility to probe and even manipulate ultra-fast electron dynamics occurring in atomic structures (Von der Linde et al, 2001;Corkum & Krausz, 2007;Mourou et al, 2007;Midorikawa, 2011). Currently, the well-known schemes to produce APs include high harmonics generation (HHG) from laser-atom interaction at moderate laser intensity (Salieres et al, 1995;Hergott et al, 2002;Takahashi et al, 2004;Nabekawa et al, 2009) or HHG from laser-solid interaction at relativistic laser intensity (Naumova et al, 2004;Quere et al, 2006;Tsakiris et al, 2006;Zheng et al, 2006;Baeva et al, 2007;Dromey et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Next generation laser facilities, such as the Extreme Light Infrastructure (ELI) [17], are designed to enhance both of these parameters. Extrapolations have been performed to predict proton production from ultra-intense laser interactions with thin targets [13].…”
Section: Future Capabilitiesmentioning
confidence: 99%